The Lazy Tour of Two Idle Apprentices - Dickens, Charles, 1812-1870; Collins, Wilkie, 1824-1889 (Salt Lake City, UT : Project Gutenberg, 1997)
"The Lazy Tour of Two Idle Apprentices" by Charles Dickens and Wilkie Collins is a humorous travel narrative written in the mid-19th century. The story follows two idle apprentices, Thomas Idle and Francis Goodchild, who escape their mundane lives for what they hope will be a carefree excursion. However, their journey quickly transforms into a comedic exploration of their contrasting personalities and views on idleness, which leads to a series of misadventures. The opening of the narrative introduces us to Idle and Goodchild as they abandon their responsibilities, longing for the simple pleasure of doing nothing. Their haphazard travel takes them from London to the northern English countryside, juxtaposing the idyllic rural landscape with their bumbling attempts at navigation and exploration. The characters are animated and engaging, with Goodchild often pushing Idle into ill-conceived plans that lead to humorous conflicts, particularly when their trip takes an unexpected turn in the rainy terrain of Cumberland, where they endeavor to climb the mountain Carrock. Their idleness and the absurdity of their situation set up a light-hearted but reflective commentary on the concept of leisure and purpose in life. (This is an automatically generated summary.)
Release date is 1997-04-01
Transcribed from the 1905 Chapman and Hall edition (_The Works of Charles Dickens_, volume 28) by David Price
Keywords: Apprentices -- Fiction; Walking -- England -- Cumbria -- Fiction; Cumbria (England) -- Description and travel -- Fiction